1972
DOI: 10.1346/ccmn.1972.0200503
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Ethylenediamine (EDA) on Montmorillonite Saturated with Different Cations—II. Hydrogen- and Ethylenediammonium-Montmorillonite: Protonation and Hydrogen Bonding

Abstract: Abstract--The form under which ethylenediamine (EDA) is adsorbed from aqueous solution by hydrogen-and ethylenediammonium-montmorillonite was studied as a function of the amount of amine present in the system. EDA added to the acid clay in quantities lower than or equal to the cation exchange capacity 9 " 2+ (C.E.C.) was exclusively adsorbed as ethylenedlammonmm (EDAH2) ion. On further addition of diamine the pH of the suspension rose to alkaline values and the monoprotonated species (EDAH § was the main charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…In contrast, the electrochemical experiments shown here suggest that addition of the 6 carbons in Co(en)33+, results in a substantially decreased observable electrostatic mechanism relative to Co(NH3)63+. This observation is consistent with that made by Knudsen and McAtee (1973) who suggested that Co(en)33+/Na § exchange with clay was not solely electrostatic in nature, The non-electrostatic retention of the complexes may occur via H-bonding (Cloos and Lauro 1972) or via substitution of ligands by the clay surface as is observed for Cu(en)32 § (Burba and McAtee 1977). Surface substitution for axial ligands results in an increase of the crystal field stabilization energy for Cu(en)32 § (Velghe et al 1977;Maes et al 1980).…”
Section: Supporting Studiessupporting
confidence: 92%
“…In contrast, the electrochemical experiments shown here suggest that addition of the 6 carbons in Co(en)33+, results in a substantially decreased observable electrostatic mechanism relative to Co(NH3)63+. This observation is consistent with that made by Knudsen and McAtee (1973) who suggested that Co(en)33+/Na § exchange with clay was not solely electrostatic in nature, The non-electrostatic retention of the complexes may occur via H-bonding (Cloos and Lauro 1972) or via substitution of ligands by the clay surface as is observed for Cu(en)32 § (Burba and McAtee 1977). Surface substitution for axial ligands results in an increase of the crystal field stabilization energy for Cu(en)32 § (Velghe et al 1977;Maes et al 1980).…”
Section: Supporting Studiessupporting
confidence: 92%
“…They showed the same features and the same modifications on heating in vacuum ( Fig. 1) as those recorded on EDA-H-montmorillonite complexes (Cloos and Laura, 1972) with amine contents lower than or equal to the CEC of the clay.…”
Section: Methodssupporting
confidence: 70%
“…Similarly, the disappearance of the broad absorption centered on 1500 cm-1 suggests that some N-H vibration is involved here, possibly 6NH~-sym. But the corresponding strong and broad stretching band, which is expected near 3200 cm-1 (Cloos and Laura, 1972) is not apparent. Therefore, it can be concluded that EDA is retained mainly in the unprotonated form.…”
Section: Unwashed Systemsmentioning
confidence: 84%
See 2 more Smart Citations